Intraoperative imprint cytology of sentinel lymph nodes in breast cancer patients: comparation with frozen section - Ivković-Kapicl, Tatjana; Vicko, Ferenc; Panjković, Milana; Radovanović, Zoran; Vasiljević, Tijana; Radovanović, Dragana; Knežević-Ušaj, Slavica (Vojnosanitetski pregled, 2021)
Background/Aim. Sentinel lymph node (SLN) biopsy has been established as the standard of care for axillary staging in patients with invasive breast carcinoma and clinically negative lymph nodes. Intraoperative assessment of sentinel lymph nodes might be done by frozen section (FS), touch imprint cytology (TIC) and one step nucleic acid amplification. The aim of this study was to review our institution's results with SLN biopsy using TIC and FS technique as intraoperative diagnostic tool for breast cancer patients. Methods. SLNs from 101 patients were examined intraoperatively by frozen hematoxylin-eosin (H&E) stain and by touch imprint cytology. Results of TIC were compared with FS and permanent histology sections. Results. The total number of dissected SLNs was 163 with a mean of 1.6 (1–4) per patient. The permanent H&E identified 19 (19%) patients with a sentinel lymph node metastasis and 82 (81%) patients with tumor-free sentinel nodes. The sensitivity/specificity rates were 73.7%/99.3%, respectively for TIC and 84.2%/100%, respectively for FS. Relevant positive/negative predictive values were 93.3%/96.6%, respectively for TIC and 100%/97.9%, respectively for FS. Conclusion. Our experience with TIC and FS for the intraoperative evaluation of SLNs is similar to the findings from previously reported studies. We detected the high specificity for both methods, but TIC technique appeared to be less sensitive than FS in detecting SLN metastases in breast cancer patients. TIC could be recommended as reasonable alternative to frozen section due to its simplicity and low cost.
Keywords: sentinel lymph node biopsy; breast neoplasms; intraoperative period; diagnostic techniques and procedures